2000
DOI: 10.1093/emboj/19.6.1187
|View full text |Cite
|
Sign up to set email alerts
|

Secreted cathepsin L generates endostatin from collagen XVIII

Abstract: Endostatin, an inhibitor of angiogenesis and tumor growth, was identified originally in conditioned media of murine hemangioendothelioma (EOMA) cells. N-terminal amino acid sequencing demonstrated that it corresponds to a fragment of basement membrane collagen XVIII. Here we report that cathepsin L is secreted by EOMA cells and is responsible for the generation of endostatin with the predicted N-terminus, while metalloproteases produce larger fragments in a parallel processing pathway. Efficient endostatin gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
282
3
7

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(296 citation statements)
references
References 39 publications
3
282
3
7
Order By: Relevance
“…In chronic lymphocytic leukemia and NHL no difference was found between endostatin plasma levels in complete remission and progressive disease. Morevoer endostatin serum levels did not correlate with disease free survival [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronic lymphocytic leukemia and NHL no difference was found between endostatin plasma levels in complete remission and progressive disease. Morevoer endostatin serum levels did not correlate with disease free survival [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Endostatin is one of the better characterized endogenously-produced angiogenesis inhibitors [3]. Endostatin has been shown to be highly effective in inhibiting angiogenesis and tumor growth [4,5]. It may mediate these biological effects by inhibiting proliferation and inducing apoptosis in endothelial cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…37 On the other hand, recent reports have demonstrated that the generation of endostatin, an inhibitor of angiogenesis and tumor growth, is catalyzed by proteolytic enzymes, including cathepsin L and matrix metalloproteases. 38,39 However, cathepsin L as well as cathepsin B has been implicated in malignant transformation, 40,41 metastatic tumor growth and poor prognosis. [42][43][44] In particular, secreted and membrane-associated cathepsins appear to play an important role in metastasis and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Karihaloo et al (2001) proposed that MMPs degraded the basement membrane at the tip of the growing ureteric bud, resulting in an accumulation of endostatin which then acted to inhibit further branching. Felbor et al (2000) also suggest that endostatin acts in a feedback mechanism during angiogenesis. We hypothesize that such a mechanism contributes to the prevention of unchecked sprouting from existing blood vessels during tumour-induced angiogenesis.…”
Section: Formation Of Antiangiogenic Molecules During Tumourinduced Amentioning
confidence: 91%
“…Cleavage of endostatin from collagen XVIII is mediated by some of the matrix metalloproteases (MMPs) (Heljasvaara et al, 2005), and, at low pH, by the protease, cathepsin L, independent of MMP activity (Felbor et al, 2000). Production of proteases such as cathepsin L and MMPs involved in the production of endostatin are known to be upregulated in the vicinity of tumour-induced angiogenesis (see, for instance, Taraboletti et al, 2002;Felbor et al, 2000;Jones et al, 1999). Additionally, it has been hypothesized that endostatin plays a role in preventing unchecked outgrowth of the developing ureteric bud.…”
Section: Formation Of Antiangiogenic Molecules During Tumourinduced Amentioning
confidence: 99%